Dramaturgi dalam Motif Sharing di Instagram pada Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Malang - Salsabillah Malicha Putri; Deny Wahyu Apriadi (Jurnal Komunikasi Nusantara, 2023)
The existence of social media made it easy for everyone to interact. The rising use of social media in Indonesia resulted in the emergence of the sharing phenomenon. This research intended to describes the motives of sharing on instagram, as well as overview of the front stage and the back stage. The method that has been employed for this research is qualitative research with type of descriptive research. The dramaturgy theory of Erving Goffman is used to describe the motives of sharing on Instagram. Based on the result of the research, there are five motives of sharing on instagram. First, the social relations in which made the students feel happy and recognized when they got likes and comments. Second, the self-representation, in this case, the students wanted to show good self-representation. Third, entertainment and learning in which coul be seen from the individuals’ behavior of sharing unique and interesting posts. Fourth, Instagram could be used as a diary that stored all activities. Fifth, the motive for expression in which students have a habit since then to tell all the activities carried out to others. The front stage is everything displayed by the individuals when they were interacting with others. The front stage consisted of the setting and the personal front. The setting is related to photo selection and the features that are used, meanwhile the personal front is related to the feed, story, caption, and their manner. Furthermore, the back stage is related to the real-life situation. Abstrak Adanya media sosial memudahkan setiap orang untuk berinteraksi. Maraknya penggunaan media sosial di Indonesia mengakibatkan munculnya fenomena sharing. Penelitian ini menggambarkan tentang motif sharing di instagram, serta gambaran panggung depan dan panggung belakang. Metode yang digunakan pada penelitian ini yaitu metode penelitian kualitatif dengan jenis penelitian deskriptif. Teori dramaturgi Erving Goffman digunakan untuk menggambarkan motif sharing di Instagram. Berdasarkan hasil penelitian terdapat lima motif sharing di Instagram. Pertama, relasi sosial yang membuat mahasiswa merasa senang dan diakui ketika mendapat like dan komentar. Kedua, representasi diri, dalam hal ini mahasiswa ingin menampilkan representasi diri yang baik. Ketiga, hiburan dan belajar yang terlihat dari perilaku individu membagikan postingan yang dirasa menarik dan unik. Keempat, Instagram bisa dijadikan buku harian yang menyimpan segala aktivitas. Kelima, motif berekspresi di mana mahasiswa memiliki kebiasaan sejak untuk menceritakan segala aktivitas yang dilakukan kepada orang lain. Panggung depan adalah sesuatu yang ditunjukkan individu ketika mereka berinteraksi dengan orang lain. Panggung depan terdiri dari setting dan personal front. Setting berkaitan dengan pemilihan foto dan fitur yang digunakan, sedangkan personal front berkaitan dengan feed, story, caption, dan sikap mereka. Selanjutnya, panggung belakang terkait dengan situasi kehidupan nyata.